Botswana: Agricultural R&D Indicators Factsheet - Flaherty, Kathleen; Mazereku, Charles; Beintema, Nienke M.; Bodilenyane, Neo Sharon; Pérez, Sandra (International Food Policy Research Institute, 2018)
This country factsheet presents key agricultural R&D indicators in a highly accessible visual display. The publication also features a more in-depth analysis of some of the key challenges that the country’s agricultural R&D system is facing, and the policy options to address these challenges.